2014
DOI: 10.2131/jts.39.821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of talaporfin sodium-mediated photodynamic therapy on cell death modalities in human glioblastoma T98G cells

Abstract: -While photodynamic therapy (PDT) is an effective treatment for glioma, induction of apoptotic cell death of glioma cells is important for ensuring efficacy and safety of PDT treatment in glioma patients, as necrotic cell death can induce late appearance of obstacles in treatment. Here, we investigated the relationship between type of cell death and PDT treatment conditions involved in laser and photosensitizer dosage in human glioblastoma T98G cells. Photosensitizer talaporfin sodium-mediated PDT (NPe6-PDT) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…33,34 The antitumor effects cannot be attributed to the photosensitizer alone or the laser alone. 35,36 The photosensitizer used in PDT is transformed from its ground state into an electronically excited state by laser light of a specific wavelength and transfers the energy directly to triplet oxygen to form singlet oxygen (a type II reaction), which exerts an antitumor effect. 4 We could capture the PDT-induced early response as high signals on DWI and low ADC values because the cell damage and microcirculatory impairment caused by PDT led to restricted diffusivity of water molecules.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 The antitumor effects cannot be attributed to the photosensitizer alone or the laser alone. 35,36 The photosensitizer used in PDT is transformed from its ground state into an electronically excited state by laser light of a specific wavelength and transfers the energy directly to triplet oxygen to form singlet oxygen (a type II reaction), which exerts an antitumor effect. 4 We could capture the PDT-induced early response as high signals on DWI and low ADC values because the cell damage and microcirculatory impairment caused by PDT led to restricted diffusivity of water molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Leist et al reported that increasing the intensity of the insult through longer exposure times or higher concentrations of the necrosis inducer can shift the dominant cell death process from apoptosis to necrosis [7]. We also previously compared the relative and absolute amounts of apoptosis and necrosis caused by low (25 μg/ml NPe6 or 5 J/cm 2 laser fluence) and high (50 μg/ml or 30 J/cm 2 laser fluence) concentrations of NPe6-PDT in T98G cells and found that numbers of apoptotic cells were decreased and necrotic cells increased with increasing concentrations of NPe6 and light [15,19]. Here, we showed that not only the apoptotic pathway but also the necroptotic pathway is limited by PDT treatment using a high concentration of NPe6.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that the efficacy of PDT using the photosensitizer TS (TS-PDT) to glioma patients in a clinical study (Akimoto et al, 2012). In vivo and in vitro studies have shown that the treatment of TS-PDT induced apoptotic and necrotic cell death in transplanted glioma Namatame et al, 2008) and cultured glioma cells (Miki et al, 2013(Miki et al, , 2014. In addition, we have also demonstrated that the treatment of TS-PDT has anti-tumor activity against not only glioblastoma cells but also malignant meningioma cells (Shinoda et al, 2017).…”
Section: Introductionmentioning
confidence: 96%